Structural Analysis of Phosphoserine Aminotransferase (Isoform 1) From Arabidopsis thaliana– the Enzyme Involved in the Phosphorylated Pathway of Serine Biosynthesis - Sekula, Bartosz (Front Plant Sci, 2018)
Phosphoserine aminotransferase (PSAT) is a pyridoxal 5′-phosphate (PLP)-dependent enzyme that catalyzes the conversion of 3-phosphohydroxypyruvate (3-PHP) to 3-phosphoserine (PSer) in an L-glutamate (Glu)-linked reversible transamination reaction. This process proceeds through a bimolecular ping–pong mechanism and in plants takes place in plastids. It is a part of the phosphorylated pathway of serine biosynthesis, one of three routes recognized in plant organisms that yield serine. In this three-step biotransformation, 3-phosphoglycerate (3-PGA) delivered from plastidial glycolysis and Calvin cycle is oxidized by 3-PGA dehydrogenase. Then, 3-PHP is subjected to transamination with Glu to yield PSer and α-ketoglutarate (AKG). In the last step of the pathway, serine is produced by the action of phosphoserine phosphatase. Here we present the structural characterization of PSAT isoform 1 from Arabidopsis thaliana (AtPSAT1), a dimeric S-shaped protein that truncated of its 71-residue-long chloroplast-targeting signal peptide. Three crystal structures of AtPSAT1 captured at different stages of the reaction: (i) internal aldimine state with PLP covalently bound to the catalytic K265, (ii) holoenzyme in complex with pyridoxamine-5′-phosphate (PMP) after transfer of the amino group from glutamate and (iii) the geminal diamine intermediate state wherein the cofactor is covalently bound to both, K265 and PSer. These snapshots over the course of the reaction present detailed architecture of AtPSAT1 and allow for the comparison of this plant enzyme with other PSATs. Conformational changes of the protein during the catalytic event concern (i) the neighborhood of K265 when the amino group is transferred to the cofactor to form PMP and (ii) movement of the gate-keeping loop (residues 391–401) upon binding of 3-PHP and PSer. The latter conformational change of the loop may likely be one of key elements that regulate catalytic activity of PSATs.